Penerapan Lean Six Sigma Untuk Mereduksi Waste Pada Proses Pengantongan Urea: Studi Pada Pabrik-6, PT. Pupuk Kaltim - Gilberth Sontanan Biu (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The urea bagging process at PT Pupuk Kaltim is a critical stage in the production chain, currently operating under a push system based on production planning. Historical data from 2021 to 2023 indicate an increasing trend in the reject product ratio at the bagging-2 unit, rising from 0.013% to 0.057%. This increase reflects the presence of process inefficiencies and waste, leading to higher operational costs, reduced production efficiency, and potential declines in customer satisfaction. Although the push system is conceptually less aligned with Lean Six Sigma principles, which emphasize a pull-based approach, Lean Six Sigma remains relevant as a structured methodology to identify waste and improve overall process performance.This study aims to analyze the root causes of product rejects and propose appropriate improvement strategies to enhance efficiency and quality in the bagging process. The DMAIC (Define, Measure, Analyze, Improve, Control) framework is employed as a systematic approach for continuous improvement. In the Define phase, Value Stream Mapping (VSM) is used to map the process flow and distinguish between value-added and non-value-added activities. The Measure phase utilizes a Pareto Chart to prioritize the most significant problems. In the Analyze phase, Root Cause Analysis (RCA) and Failure Mode and Effect Analysis (FMEA) are applied to identify root causes and assess the risk level of process failures. The Improve phase focuses on developing corrective actions, such as machine modifications and refinement of work procedures. Finally, the Control phase employs Control Charts to ensure process stability after improvements are implemented. The results of this study are expected to provide a foundation for continuous improvement efforts in enhancing the efficiency and quality of the urea bagging process at PT Pupuk Kaltim.